Time series and trend analysis of brucellosis in Oskou county, EastAzerbaijan: 2007-2016 - Hosein Rafiemanesh (Health Promotion Perspectives, 2019)
Background: The epidemiology of human brucellosis has drastically changed in recent years. This study aims to assess trend in brucellosis in the Oskou county, East Azerbaijan, Iran. Methods: This cross-sectional study was conducted on all confirmed brucellosis cases over the period between 2007 and 2016 in Oskuo county. We use crude incidence rate (CIR) per100000 persons and carried out Joinpoint regression analysis to describe brucellosis trend over the study period. Also, we used ARIMA model to predict trend and number of new brucellosis cases for the coming years. Results: More than 90% (92.5%; 95% CI: 89.9-95.1) of brucellosis cases were in rural areas over the study period. In recorded cases, 60.5% (95% CI: 55.6-65.4) of total cases were men and 39.5% (95% CI: 34.6-44.4) of total cases were women. The mean age of men was 33.85(SD=19.72) years and the mean age of women was 35.88 (SD=17.26) years old. Majority of brucellosis cases occurred in spring. CIRs for the rural and urban areas were 47.62 to132.20 and zero to 18.55, respectively. The CIR for rural area had decreasing trend to 2011 and increasing for 2011-2017. Conclusion: Based-on time series analysis, the number of new cases in the future years has fixed trend and the most number of incident cases will be occurred between third to fifth months in each years.